2019
DOI: 10.1038/s41598-018-37024-5
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian plasma fetuin-B is a selective inhibitor of ovastacin and meprin metalloproteinases

Abstract: Vertebrate fetuins are multi-domain plasma-proteins of the cystatin-superfamily. Human fetuin-A is also known as AHSG, α2-Heremans-Schmid-glycoprotein. Gene-knockout in mice identified fetuin-A as essential for calcified-matrix-metabolism and bone-mineralization. Fetuin-B deficient mice, on the other hand, are female infertile due to zona pellucida ‘hardening’ caused by the metalloproteinase ovastacin in unfertilized oocytes. In wildtype mice fetuin-B inhibits the activity of ovastacin thus maintaining oocytes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(57 citation statements)
references
References 72 publications
1
56
0
Order By: Relevance
“…We concluded from these results that metalloproteinases, in particular astacin-type proteinases, are likely candidates for the observed HyWnt3-His processing activity. To confirm this notion, we tested the proteolytic activity of HL on HyWnt3 in the presence of recombinant mammalian Fetuin-B, which was recently shown to function as a highly specific physiological inhibitor of astacin-type proteinases like ovastacin [19]. As shown in Fig.…”
Section: Fig S1bmentioning
confidence: 93%
“…We concluded from these results that metalloproteinases, in particular astacin-type proteinases, are likely candidates for the observed HyWnt3-His processing activity. To confirm this notion, we tested the proteolytic activity of HL on HyWnt3 in the presence of recombinant mammalian Fetuin-B, which was recently shown to function as a highly specific physiological inhibitor of astacin-type proteinases like ovastacin [19]. As shown in Fig.…”
Section: Fig S1bmentioning
confidence: 93%
“…Protein hFB with a C-terminal hexahistidine-tag, thus spanning residues C 16 -P 382 -IEGRHHHHHH, was expressed and secreted to the extracellular medium by mammalian ExpiCHO-S cells according to the manufacturer’s instructions (ThermoFisher Scientific) as previously reported 35 . Human meprin β was obtained as a zymogen as described 51 and activated with trypsin 52 .…”
Section: Methodsmentioning
confidence: 99%
“…To complement these studies, we here report the crystal structure of the complex between the human ortholog of fetuin-B (hFB), which is the physiologically relevant species for studying human fertility 42 , and 202-residue mature crayfish astacin, which is a useful model for the 197-residue catalytic domain of human ovastacin (35% sequence identity; 48% similarity; see also 35 ). These studies revealed unexpected differences with mFB in terms of proteolytic susceptibility and the spatial arrangement of the cystatin domains, which enabled us to identify dispensable structural elements for inhibition.…”
Section: Introductionmentioning
confidence: 99%
“…First identified as a putative mammalian hatching enzyme (Quesada, Sánchez, Alvarez, & López‐Otín, 2004), ovastacin contains a unique heptapeptide motif that ensures its localization in the CGs as a proenzyme of 44 kDa (Burkart et al, 2012; Xiong, Zhao, Beall, Sadusky, & Dean, 2017); following oocyte activation, the protein is released as an active enzyme of 29 kDa that lacks the propeptide as well as a C‐terminal fragment (Körschgen et al, 2017). On the basis of in vitro cleavage studies with plasminogen that was either activated by trypsin or combined with tissue plasminogen activator (t‐PA; Karmilin et al, 2019)—a molecule that is also found in the oocyte CGs (Huarte, Belin, & Vassalli, 1985)—it is thought that in vivo maturation of ovastacin depends on the action of one or more serine proteases (Karmilin et al, 2019; Figure 2).…”
Section: Cg Exocytosis Modifies the Zp After Fertilizationmentioning
confidence: 99%